Negative electrode material, its manufacturing method, and lithium ion battery

By forming a porous silicon-carbon composite layer on the surface of the silicon-based material, the problems of silicon volume expansion and poor cycle stability of the negative electrode material of lithium-ion battery are solved, and high energy density and long-life battery performance is achieved.

JP7670275B2Active Publication Date: 2025-04-30BTR NEW MATERIAL GRP CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023547158
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-09-07
Publication Date
2025-04-30
Estimated Expiration
2042-09-07

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material, silicon, expands in large volume during charging and discharging, resulting in poor cycle stability and difficult to meet the needs of high energy density and long life.

Method used

The negative electrode material adopts a core-surface composite structure, the core is a silicon-based material, and the surface is covered with a porous silicon-carbon composite layer containing a carbon matrix and silicon particles dispersed in the carbon matrix. The carbon matrix is ​​formed by thermal reaction and the metal oxide is removed to form a carbon matrix with holes and silicon particles embedded therein.

Benefits of technology

It effectively suppresses the volume expansion of silicon-based materials, improves electrochemical performance, enhances the conductivity and cyclic stability of the negative electrode materials, and meets the high energy density and fast charging and discharge requirements of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670275000002
    Figure 0007670275000002
  • Figure 0007670275000003
    Figure 0007670275000003
  • Figure 0007670275000004
    Figure 0007670275000004
Patent Text Reader

Abstract

The present application relates to the field of negative electrode materials, and provides a negative electrode material and a method for producing the same, and a lithium ion battery. [Solution] The anode material has a core-shell structure and includes a core and a porous silicon-carbon composite layer distributed on at least a part of the surface of the core, the core includes a silicon-based material, the porous silicon-carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores. The anode material of the present invention has high electrical conductivity, high capacity, can effectively suppress volume expansion, and improves the electrochemical properties of a battery including the anode material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention claims priority to a Chinese patent application filed with the State Intellectual Property Office of the People's Republic of China on September 30, 2021, bearing application number 2021111601577 and entitled "Negative electrode material and its manufacturing method, and lithium ion battery," the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to the technical field of anode materials, and more particularly to anode materials and methods for producing the same, and lithium ion batteries. [Background technology]

[0003] Silicon is the second most abundant element in the earth's crust and a common semiconductor material, which has become an essential technological foundation for modern high-tech society. Elemental silicon is widely used in the fields of energy, semiconductors, silicone and metallurgy, and plays an important role. Currently, the anode materials of mature commercial lithium-ion batteries are mainly graphite-based carbon materials, but the theoretical lithium storage capacity of carbon materials is only 372mAh / g, which cannot meet the demand for high energy density materials. As an anode material for lithium-ion batteries, silicon has a high theoretical capacity (about 4200mAh / g), which is 10 times the capacity of commercial graphite, and has great potential in terms of energy storage. However, silicon anode materials have a large volume expansion (>300%) during the process of releasing and absorbing lithium, and the high volume change effect leads to poor cycle stability, which has led to a certain distance from practical use.

[0004] Therefore, how to prepare anode materials with stable structure, high capacity, low expansion, and excellent cycle performance is a difficult problem in the field of lithium-ion batteries. Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above, the present invention provides a negative electrode material that has high conductivity, high capacity, and can effectively suppress volume expansion, and can improve the electrochemical properties of a battery containing the negative electrode material, a method for producing the same, and a lithium-ion battery.

[0006] In a first aspect, an embodiment of the present invention provides an anode material comprising a core and a porous silicon carbon composite layer distributed on at least a portion of a surface of the core, the core comprising a silicon-based material, and the porous silicon carbon composite layer comprising a carbon matrix having voids and silicon particles dispersed within the carbon matrix.

[0007] In some embodiments, at least a portion of the silicon particles are dispersed in pores in the carbon matrix.

[0008] In some embodiments, the core is a silicon-based material.

[0009] In some embodiments, the silicon-based material comprises at least one of elemental silicon, a silicon alloy, and an oxide of silicon.

[0010] In some embodiments, the silicon-based material comprises a silicon alloy, the silicon alloy comprising at least one selected from a silicon-tin alloy, a silicon-lithium alloy, and a silicon-germanium alloy.

[0011] In some embodiments, the silicon-based material comprises a silicon oxide, and the silicon oxide is SiOx(0 <x≦2)である。

[0012] In some embodiments, the silicon-based material has at least one of the following shapes: particulate, spherical, roughly spherical, wire-like, and tubular.

[0013] In some embodiments, the silicon-based material has a median diameter of 0.1 μm to 15 μm.

[0014] In some embodiments, the silicon-based material has a median diameter of 0.5 μm to 5 μm.

[0015] In some embodiments, the composite layer has a thickness of from 0.01 μm to 10 μm.

[0016] In some embodiments, the ratio of the median diameter of the silicon-based material to the thickness of the composite layer is (1-10):1.

[0017] In some embodiments, the negative electrode material has a porosity of 10% to 50%.

[0018] In some embodiments, the content of the carbon matrix in the porous silicon carbon composite layer is 5% by mass to 80% by mass.

[0019] In some embodiments, the carbon matrix has pores, the pores including macropores and mesopores.

[0020] In some embodiments, the carbon matrix has pores, the pores including macropores and mesopores, and the ratio of the pore volumes of the macropores and the mesopores is (0.5-5):1.

[0021] In some embodiments, the silicon particles have a median diameter of 1 nm to 500 nm.

[0022] In some embodiments, the silicon particles have a median diameter of 10 nm to 100 nm.

[0023] In some embodiments, the mass ratio of the silicon particles to the silicon-based material is (0.3-0.7:1).

[0024] In some embodiments, the carbon matrix comprises solid portions and pores, with at least a portion of the silicon particles dispersed in the solid portions.

[0025] In some embodiments, the carbon matrix comprises solid portions and pores, with a portion of the silicon particles dispersed in the pores and a portion of the silicon particles dispersed in the solid portions.

[0026] In some embodiments, the carbon matrix includes a solid portion and pores, a portion of the silicon particles are dispersed in the pores, and a portion of the silicon particles are dispersed in the solid portion, and the molar ratio of the silicon particles dispersed in the solid portion to the silicon particles dispersed in the pores is 1:(0.5 to 3).

[0027] In some embodiments, when the compression rate of the composite layer reaches 50%, the resilience rate of the composite layer is 90% or more.

[0028] In some embodiments, the negative electrode material further includes a coating layer formed on at least a portion of a surface of the composite layer.

[0029] In some embodiments, the coating layer comprises at least one of a carbon material, a metal oxide, a nitride, and a conductive polymer.

[0030] In some embodiments, the coating layer comprises a carbon material, the carbon material comprising at least one of graphene, soft carbon, hard carbon, and amorphous carbon.

[0031] In some embodiments, the coating layer comprises a metal oxide, the metal oxide comprising at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.

[0032] In some embodiments, the coating layer comprises a nitride, the nitride comprising at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride, and carbon nitride.

[0033] In some embodiments, the coating layer comprises a conductive polymer, the conductive polymer comprising at least one of polyaniline, polyacetylene, polypyrrole, polythiophene, poly(3-hexylthiophene), polyp-styrene, polypyridine, and polyphenylene vinylidene.

[0034] In some embodiments, the coating layer has a thickness of 3 nm to 200 nm.

[0035] In some embodiments, the negative electrode material has a median diameter of 0.1 μm to 20 μm.

[0036] In some embodiments, the negative electrode material has a specific surface area of ​​1.0 m 2 / g~50m 2 / g.

[0037] In some embodiments, the negative electrode material has a powder tap density of 1.0 g / m 3 ~1.8g / m 3 It is.

[0038] In some embodiments, the negative electrode material has an oxygen content of less than 20% by weight.

[0039] In a second aspect, an embodiment of the present invention provides a method for making an anode material, comprising:

[0040] A step of producing a composite including a silicon-based material and an AxSi alloy (wherein A is an active metal and X=1 to 3) formed on at least a portion of the surface of the silicon-based material; and mixing the composite with a carbon source, followed by a thermal reaction to convert at least a portion of the AxSi alloy into an oxide of metal A, and removing the oxide of metal A to obtain a silicon-carbon composite material.

[0041] In some embodiments, the silicon-based material comprises at least one of elemental silicon, a silicon alloy, and an oxide of silicon.

[0042] In some embodiments, the silicon-based material comprises a silicon alloy, the silicon alloy comprising at least one selected from a silicon-tin alloy, a silicon-lithium alloy, and a silicon-germanium alloy.

[0043] In some embodiments, the silicon-based material comprises a silicon oxide, and the silicon oxide is SiOx(0 <x≦2)である。

[0044] In some embodiments, the silicon-based material has at least one of the following shapes: particulate, spherical, roughly spherical, wire-like, and tubular.

[0045] In some embodiments, the silicon based material is spherical or nearly spherical in shape.

[0046] In some embodiments, the silicon-based material has a median diameter of 0.1 μm to 15 μm.

[0047] In some embodiments, the silicon-based material has a median diameter of 1 μm to 5 μm.

[0048] In some embodiments, the active metal A comprises at least one of Mg, Al, Ca, and Zn.

[0049] In some embodiments, the molar ratio of the silicon-based material to the active metal A is 1:(0.1 to 3).

[0050] In some embodiments, the step of producing the composite includes alloying the silicon-based material with the active metal A in a protective atmosphere.

[0051] In some embodiments, the step of producing the composite includes alloying the silicon-based material with the active metal A in a protective atmosphere, where the alloying reaction is carried out at a temperature of 400°C to 900°C for an incubation time of 1 hour to 24 hours.

[0052] In some embodiments, the step of producing the composite includes alloying the silicon-based material with the active metal A in a protective atmosphere, wherein the alloying reaction has a heating rate of 1° C. / min to 10° C. / min.

[0053] In some embodiments, the step of producing the composite includes alloying the silicon-based material with the active metal A in a protective atmosphere, where the protective atmosphere includes at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas.

[0054] In some embodiments, the AxSi alloy formed on at least a portion of the surface of the silicon-based material has a thickness of 0.05 μm to 20 μm.

[0055] In some embodiments, the complex has a median diameter of 0.1 μm to 20 μm.

[0056] In some embodiments, the carbon source comprises an organic carbon source.

[0057] In some embodiments, the carbon source comprises an organic carbon source, which is solid under room temperature conditions and comprises at least one of aldehydes, phenols, and their corresponding halogenated compounds, each of which has a boiling point of less than 650° C.

[0058] In some embodiments, the carbon source comprises an inorganic carbon source.

[0059] In some embodiments, the carbon source comprises an inorganic carbon source, and the inorganic carbon source comprises a carbon-containing inorganic salt.

[0060] In some embodiments, the step of performing a thermal reaction after mixing the composite with a carbon source is performed in a protective atmosphere, the protective atmosphere comprising at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas.

[0061] In some embodiments, the 、 metal A Oxide of Removing the thermal reaction products includes pickling the thermal reaction products with an acid solution.

[0062] In some embodiments, the 、 metal A Oxide of Removing includes pickling the thermal reaction product with an acid solution, the acid solution including at least one of hydrochloric acid, nitric acid, and sulfuric acid.

[0063] In some embodiments, the molar ratio of the complex to the carbon source is 1:(0.01 to 10).

[0064] In some embodiments, the thermal reaction is at a temperature between 200°C and 950°C.

[0065] In some embodiments, the thermal reaction has an incubation time of 1 hour to 24 hours.

[0066] In some embodiments, the thermal reaction has a temperature rise rate of 1° C. / min to 20° C. / min.

[0067] In some embodiments, the method further comprises forming a coating layer on a surface of the silicon carbon composite material to obtain a negative electrode material.

[0068] In some embodiments, the step of forming a coating layer on the surface of the silicon carbon composite comprises sintering a mixture comprising the silicon carbon composite and polymer particles under a vacuum condition to form the coating layer.

[0069] In some embodiments, the polymer particles include at least one of asphalt, resin, polyester-based polymer, and polyamide-based polymer.

[0070] In some embodiments, the mass ratio of the polymer particles to the silicon carbon composite material is 1:(0.1-10).

[0071] In some embodiments, the sintering is performed at a temperature of 600°C to 1000°C.

[0072] In some embodiments, the sintering is performed with an incubation time of 1 hour to 24 hours.

[0073] In some embodiments, the sintering is performed at a temperature increase rate of 1° C. / min to 20° C. / min.

[0074] In some embodiments, the vacuum condition has a vacuum level of less than 0.1 Mpa.

[0075] In some embodiments, the step of forming a coating layer on the surface of the silicon carbon composite material comprises synthesizing a polymer on the surface of the silicon carbon composite material using a chemical synthesis method to form a coating layer.

[0076] In some embodiments, the polymer comprises at least one of a resin-based polymer and a polyester-based polymer;

[0077] In some embodiments, the step of forming a coating layer on the surface of the silicon carbon composite material comprises forming a coating layer on the surface of the silicon carbon composite material by chemical vapor deposition of an organic carbon source.

[0078] In a third aspect, the present invention provides a lithium-ion battery comprising an anode material according to the first aspect or produced by the method according to the second aspect.

[0079] The technical means of the present application has at least the following beneficial effects:

[0080] (1) The negative electrode material of the present invention is provided with a porous silicon-carbon composite layer as a buffer layer on the surface of a silicon-based material core, the porous silicon-carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, the pores can effectively mitigate the volume expansion of the silicon-based material and can be a flexible conductor, the porous silicon-carbon composite layer provides a transport path for ions and electrons, strengthens the electrical conductivity between the silicon-based material and the outside, and improves the multiplication performance. In addition, the silicon particles are absorbed in the carbon matrix, that is, the silicon particles are coated with the carbon matrix, thereby improving the electrical conductivity of the silicon particles, and thus improving the multiplication performance of the negative electrode material, and meeting the demand for realizing the rapid charging characteristics of the battery.

[0081] (2) According to the method for producing the negative electrode material of the present invention, a layer of silicon alloy AxSi is formed on the surface of the silicon-based material by alloying the silicon-based material with the active metal A, that is, a complex is obtained in which AXSi covers the silicon-based material, and the complex is thermally reacted with a carbon source to convert at least a part of the AxSi alloy into an oxide of metal A, and the oxide of metal A is removed, and a carbon matrix having pores is formed on the surface of the silicon-based material, and the silicon particles obtained by reduction are dispersed in the carbon matrix, and the pores of the bulky carbon matrix can effectively relieve the volume expansion of the silicon-based material and can become a flexible conductor, providing more transport paths for ions and electrons, enhancing the conductivity between the core and the outside, and improving the multiplication performance. The production method of the present invention is simple and easy to carry out, and can effectively solve the problems of large volume expansion and low conductivity of the negative electrode material, thereby improving the electrochemical properties of the battery containing the negative electrode material. [Brief description of the drawings]

[0082] The present invention will now be further described with reference to the drawings and examples. [Figure 1] FIG. 1 is a schematic diagram of the structure of a negative electrode material according to the present invention. [Diagram 2] 2 is a schematic diagram of a structure in which silicon particles according to the present invention are occluded in pores 22. FIG. [Diagram 3] FIG. 2 is a structural schematic diagram of a manufacturing flow chart of a negative electrode material according to one embodiment of the present invention. [Figure 4] 2 is a flowchart for producing a negative electrode material according to the present invention. [Diagram 5] 1 is a scanning electron microscope (SEM) photograph of the negative electrode material prepared in Example 1 of the present invention. [Figure 6] 1 is a Raman spectrum of the negative electrode material produced in Example 1 of the present invention. [Figure 7] 1 is an XRD chart of the negative electrode material produced in Example 1 of the present invention. [Figure 8] FIG. 2 is a cycle characteristic curve diagram of the negative electrode material produced in Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0083] In order to make the technical solution of the present application more understandable, the embodiments of the present invention are described in detail below with reference to the drawings.

[0084] It is apparent that the described embodiments are only some of the embodiments of the present invention, and are not all of the embodiments. Based on the embodiments in this application, all other embodiments that a person skilled in the art can make without any creative effort fall within the scope of protection of this application.

[0085] The terms used in the embodiments of the present application are used only to describe specific embodiments and are not intended to limit the present invention. The singular forms "a", "one", "the", and "the" used in the embodiments and claims of the present invention are intended to include the plural forms unless the context clearly indicates otherwise.

[0086] It should be understood that the term "and / or" as used herein is only to describe the relation between related objects, and indicates that three kinds of relations can exist. For example, A and / or B can indicate three kinds of situations, namely, A exists alone, A and B exist together, and B exists alone. Also, the character " / " in this specification generally indicates that the related objects before and after are in an "or" relationship.

[0087] An embodiment of the present invention provides a negative electrode material, and a structural schematic diagram of the negative electrode material is shown in Figure 1. The negative electrode material has a core-shell structure, and includes a core 1 and a porous silicon carbon composite layer 2 distributed on at least a part of the surface of the core 1, the core 1 includes a silicon-based material, the porous silicon carbon composite layer 2 includes a carbon matrix 21 and silicon particles 23 dispersed in the carbon matrix 21, and the carbon matrix 21 has pores 22.

[0088] In the above technical means, a porous silicon carbon composite layer 2 is installed on the surface of a silicon-based material core 1 as a buffer layer, and the porous silicon carbon composite layer 2 includes a carbon matrix 21 and silicon particles 23 dispersed in the carbon matrix 21, the carbon matrix 21 has pores 22, the pores 22 can effectively mitigate the volume expansion of the silicon-based material and can be a flexible conductor, and the porous silicon carbon composite layer 2 can provide a transport path for ions and electrons, strengthen the conductivity between the core 1 and the outside, and improve the multiplication performance. In addition, the silicon particles 23 are occluded in the carbon matrix 21, that is, a method is adopted in which the silicon particles 23 are coated with the carbon matrix 21. This can improve the conductivity of the silicon particles, thereby improving the multiplication performance of the negative electrode material, and meeting the demand for realizing the rapid charging characteristics of the battery. In addition, since the silicon particles 23 are dispersed in the carbon matrix 21, it is possible to avoid the structure of the negative electrode material being destroyed as a whole due to the aggregation of silicon particles and the concentration of stress.

[0089] In some embodiments, at least a portion of the silicon particles 23 is dispersed in the pores 22 of the carbon matrix 21. Fig. 2 is a structural schematic diagram of the present invention in which the silicon particles are dispersed in the pores 22. As can be understood, when the silicon particles 23 are dispersed in the pores 22, the silicon particles 23 are not completely filled, and a certain space is left in the pores 22 to ease the volume expansion of the silicon particles 23, thereby preventing the entire negative electrode material from being destroyed by the volume expansion, and at the same time reducing the expansion of the electrode film, thereby improving the safety of the battery.

[0090] In some embodiments, the carbon matrix 21 includes a solid portion and voids 22 distributed in the solid portion, at least a portion of the silicon particles 23 is embedded in the solid portion, and a portion of the silicon particles 23 is embedded in the solid portion. The silicon particles 23 are embedded in the solid portion, i.e., the solid portion of the carbon matrix 21 is tightly wrapped around the surface of the silicon particles 23.

[0091] In some embodiments, some of the silicon particles 23 were dispersed in the pores and some of the silicon particles 23 were embedded in the solid portion.

[0092] As will be understood, the silicon particles 23 may be dispersed only in the solid portion of the carbon matrix 21, or may be dispersed only in the pores 22 of the carbon matrix 21, or the silicon particles 23 may be present in both the solid portion and the pores 22. When the silicon particles 23 are present in both the solid portion and the pores 22, the amount of silicon supported in the negative electrode material can be significantly improved, and the problem of the silicon particles being non-uniformly dispersed in the carbon material can be effectively solved, thereby improving the effective utilization rate of the silicon particles, which in turn improves the tap density and specific capacity of the entire negative electrode material, and improves the energy density of the entire battery material.

[0093] The present invention can meet the demand for high-magnification and low-expansion negative electrode material products by controlling the content of silicon particles at different positions of the porous silicon carbon composite layer 2.

[0094] In some embodiments, the core comprises a silicon-based material.

[0095] In some embodiments, the silicon-based material comprises at least one of elemental silicon, a silicon alloy, and an oxide of silicon.

[0096] In some embodiments, the silicon alloy comprises at least one selected from a silicon tin alloy, a silicon lithium alloy, and a silicon germanium alloy.

[0097] In some embodiments, the silicon oxide is SiOx(0 <x≦2)である。

[0098] In some embodiments, the silicon-based material has at least one of the following shapes: particulate, spherical, roughly spherical, wire-like, and tubular.

[0099] In some embodiments, the silicon based material is spherical or nearly spherical in shape.

[0100] In some embodiments, the median diameter of the silicon-based material is 0.1 μm to 15 μm, specifically, 0.1 μm, 0.2 μm, 0.3 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm, etc., and of course, other values ​​within the above range are also possible, and are not limited here.Preferably, the median diameter of the silicon-based material is 0.5 μm to 5 μm.

[0101] In some embodiments, the thickness of the porous silicon carbon composite layer 2 is 0.01 μm to 10 μm. Specifically, the thickness of the porous silicon carbon composite layer 2 may be 0.01 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc., and may of course be other values ​​within the above range, and is not limited here. If the thickness of the porous silicon carbon composite layer 2 is smaller than 0.01 μm, it is difficult to support the silicon particles 23, and if the thickness of the porous silicon carbon composite layer 2 is larger than 10 μm, the thickness of the porous silicon carbon composite layer 2 becomes large, the transmission efficiency of lithium ions decreases, and the overall performance of the negative electrode material is reduced. Preferably, the thickness of the porous silicon carbon composite layer 2 is 0.5 μm to 5 μm. As can be seen, the thickness of the porous silicon carbon composite layer 2 of the present invention coincides with the thickness of the carbon matrix 21, which is also 0.01 μm to 10 μm.

[0102] In some embodiments, the ratio of the median diameter of the silicon-based material to the thickness of the porous silicon carbon composite layer is (1-10):1, specifically, it may be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, etc., and of course, it may be other values ​​within the above range, and is not limited here. Preferably, the ratio of the median diameter of the silicon-based material 1 to the thickness of the porous silicon carbon composite layer 2 is (1-3):1. The present application can control the ratio of the thickness of the porous silicon carbon composite layer 2 to the median diameter of the silicon-based material 1 to play a good conductive role for the silicon-based material 1 with a large size range, and can effectively alleviate the volume expansion of the silicon-based material 1 without losing electrical contact.

[0103] In some embodiments, the negative electrode material has a porosity of 10% to 50%, specifically, the porosity of the negative electrode material may be 10%, 20%, 30%, 40%, 50%, etc., and of course may be other values ​​within the above range, and is not limited here. By controlling the porosity of the negative electrode material to the above range, the volume expansion space of the silicon particles 23 and the silicon-based material can be filled. Preferably, the negative electrode material has a porosity of 20% to 40%. As will be understood, the porosity refers to the ratio of the pore volume in the negative electrode material to the total volume of the negative electrode material.

[0104] In some embodiments, the content of the carbon matrix in the porous silicon carbon composite layer is 5% by mass to 80% by mass, specifically, it may be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70% and 80%, etc., and of course, it may be other values ​​within the above range, and is not limited here. As can be understood, the negative electrode material of the present invention can improve its capacity without destroying the structure of the negative electrode material by selecting the carbon matrix 21 as a carrier for the silicon particles 23. By controlling the content of the carbon matrix 21 in the porous silicon carbon composite layer 2 within the above range, the silicon particles 23 can be well accommodated, and at the same time, the porous silicon carbon composite layer 2 can tightly and firmly wrap the silicon-based material 1, and avoid the loss of electrical contact between the silicon-based material and the porous silicon carbon composite layer 2 due to the volume change after silicon absorbs lithium.

[0105] In some embodiments, the molar ratio of silicon particles embedded in the solid part to silicon particles dispersed in the pores is 1: (0.5-3), specifically, it may be 1:0.5, 1:0.8, 1:1, 1:1.5, 1:1.8, 1:2, 1:2.5, 1:2.8 or 1:3, etc., not limited thereto. By controlling the silicon content at two positions, it is possible to meet the demand for silicon carbon products with high magnification and low expansion, and to achieve a balance between high magnification and low expansion. In particular, when the molar occupancy rate of silicon particles in the solid part is high within the above-mentioned limited range, the silicon particles embedded in the solid part are completely wrapped by the carbon matrix, which improves the conductivity of silicon particles, improves the magnification performance of the composite material, and meets the demand for realizing the rapid charging characteristics of the battery. When the molar occupancy of the silicon particles dispersed in the pores is high, a certain amount of space is left in the pores to alleviate the volume expansion of the silicon particles, thereby preventing the entire negative electrode material from being destroyed by the volume expansion, and at the same time reducing the expansion of the electrode film, thereby improving the safety of the battery.

[0106] In some embodiments, when the compression ratio of the porous silicon carbon composite layer reaches 50%, the repulsion ratio of the porous silicon carbon composite layer is 90% or more, specifically, the repulsion ratio of the porous silicon carbon composite layer may be 91%, 93%, 95%, 98%, etc. The repulsion ratio of the porous silicon carbon composite layer is controlled to 90% or more to avoid the material being pulverized or losing electrical contact with the silicon-based material due to the volume expansion of the negative electrode material.

[0107] In some embodiments, the carbon matrix 21 has pores 22, which include macropores and mesopores.

[0108] As will be understood, macropores are pores with a pore diameter of more than 50 nm, and mesopores are pores with a pore diameter of 2 nm to 50 nm. The ratio of the pore volume of macropores to mesopores is (0.5 to 5): 1, specifically, the ratio of the pore volume of macropores to mesopores is 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1 and 5: 1, etc., and may of course be other values ​​within the above range, and is not limited here. The pores 22 of the present invention have abundant macropores and mesopores, and the volume expansion of the silicon-based material 1 can be relaxed by compressing the pores 22, and the silicon particles in the pores 22 also have sufficient space to relax the volume expansion. In addition, due to the presence of the pores 22, the expansion-contraction characteristics of the silicon particles 23 after releasing and absorbing lithium can be synchronized with the expansion behavior or contraction behavior of the silicon-based material 1, and good electrical contact with the silicon-based material 1 can be always maintained, ensuring excellent electron transport performance.

[0109] In some embodiments, the median diameter of the silicon particles is 1 nm to 500 nm, specifically, 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 400 nm or 500 nm, etc., and of course, other values ​​within the above range are also possible, and are not limited here. As can be understood, the median diameter of the silicon particles is controlled within the above range, and its function is to avoid the material being powdered due to the volume expansion of the silicon particles during the lithium absorption process, thereby destroying the structure. Preferably, the median diameter of the silicon particles is 5 nm to 200 nm. More preferably, the median diameter of the silicon particles is 10 nm to 100 nm.

[0110] In some embodiments, the mass ratio of silicon particles to the silicon-based material is (0.3-0.7):1, specifically, it can be 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, etc., and of course, it can be other values ​​within the above range, and is not limited here.By controlling the mass ratio of silicon particles to silicon-based material within the above range, it can ensure that the distribution of silicon element in the negative electrode material has a certain concentration gradient, that is, the distribution of silicon in the negative electrode material is gradually reduced in concentration from the inside to the outside, thereby ensuring that the diffusion of lithium ions has a uniform concentration gradient, and avoid the problem that the concentration during lithium ion diffusion is non-uniform, which leads to electrochemical polarization and ultimately deteriorates electrochemical performance.

[0111] In some embodiments, the negative electrode material further includes a coating layer 3 formed on at least a part of the surface of the porous silicon carbon composite layer 2. As can be understood, the provision of the coating layer 3 can, on the one hand, avoid the reduction in initial efficiency and capacity caused by the electrolyte entering the inside of the negative electrode material and causing side reactions, and, on the other hand, the coating layer 3 cooperates with the composite layer 2 to alleviate the volume expansion of the silicon-based material, reduce the volume expansion of the entire negative electrode material, and reduce the swelling of the electrode strip.

[0112] In some embodiments, the coating layer 3 comprises at least one of a carbon material, a metal oxide, a nitride, and a conductive polymer.

[0113] In some embodiments, the carbon material comprises at least one of graphene, soft carbon, hard carbon and amorphous carbon.When the coating layer is a carbon material, the inner porous silicon-carbon composite layer comprises a carbon matrix and silicon particles, and the outer coating layer is a carbon material, and the double carbon layer can improve the conductivity of the negative electrode material, so that the negative electrode material exhibits advantages such as high capacity, long cycle life, high rate characteristics and low expansion, and can be widely used in the field of high-performance lithium-ion battery negative electrodes.

[0114] In some embodiments, the metal oxide comprises at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.

[0115] In some embodiments, the nitride comprises at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride, and carbon nitride.

[0116] In some embodiments, the coating layer comprises a conductive polymer, the conductive polymer comprising at least one of polyaniline, polyacetylene, polypyrrole, polythiophene, poly(3-hexylthiophene-2,5-diyl), polyparaphenylenevinylene, polypyridine, and polyphenylenevinylene.

[0117] In some embodiments, the thickness of the coating layer is 3 nm to 200 nm, specifically, it may be 3 nm, 5 nm, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, etc., and of course, it may be other values ​​within the above range, and is not limited here.Preferably, the thickness of the coating layer is 5 nm to 50 nm, and as can be understood, the coating layer can reduce the contact between silicon and the electrolyte, reduce the generation of the passivation film, increase the conductivity of the negative electrode material, suppress the volume expansion of the negative electrode material, and improve the reversible capacity and cycle performance of the battery.

[0118] In some embodiments, the coating layer has a porosity of 2% to 10%, specifically, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%, etc., and may of course be other values ​​within the above range, and are not limited here. As will be understood, the porosity of the coating layer is smaller than the porosity of the porous silicon carbon composite layer (10% to 50%), and the coating layer is a dense layer relative to the porous silicon carbon composite layer, and a coating layer of a certain thickness can effectively block the intrusion of the electrolyte. Preferably, the coating layer has a porosity of 5% to 10%. In addition, the ratio of the pore volume of the coating layer to the pore volume of the entire negative electrode material being smaller than 50% helps the coating layer to block the electrolyte and reduce the swelling of the electrode piece.

[0119] In some embodiments, the median diameter of the negative electrode material is 0.1 μm to 20 μm, specifically, 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc., and may be other values ​​within the above range, and are not limited here. Preferably, the median diameter of the negative electrode material is 0.1 μm to 10 μm, and more preferably, the median diameter of the negative electrode material is 1 μm to 5 μm. As will be understood, controlling the average particle size of the negative electrode material within the above range contributes to improving the cycle characteristics of the negative electrode material.

[0120] In some embodiments, the specific surface area of ​​the negative electrode material is less than 1.0 m 2 / g~50m 2 / g, specifically, the specific surface area of ​​the negative electrode material is 1.0 m 2 / g, 1.5m 2 / g, 10m 2 / g, 20m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, etc., and of course may be other values ​​within the above range, and are not limited here. As will be understood, controlling the specific surface area of ​​the negative electrode material within the above range is advantageous in suppressing the volume expansion of the negative electrode material and improving the cycle performance of the negative electrode material.

[0121] In some embodiments, the tap density of the powder of the negative electrode material is 1.0 g / cm 3 ~1.8g / cm 3 Specifically, the tap density of the powder of the negative electrode material is 1.0 g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.1g / cm 3 and 1.8 g / cm 3 etc., and of course may be other values, and preferably the tap density of the powder of the negative electrode material is 1.3 g / cm 3 ~1.6g / cm 3 It is.

[0122] In some embodiments, the oxygen content in the negative electrode material is 20% by weight or less. As will be appreciated, if the oxygen content in the negative electrode material is too high, the initial efficiency of the negative electrode material will decrease.

[0123] In a second embodiment, the present application provides an embodiment of a negative electrode material according to the present application, as shown in FIG. 3 and FIG. 4, which are a structural schematic diagram and a manufacturing flow chart of the negative electrode material according to the present application, respectively: A step S110 of producing a composite including a silicon-based material and an AxSi alloy (wherein A is an active metal and X=1 to 3) formed on at least a portion of the surface of the silicon-based material; and a step S120 of mixing the composite with a carbon source, followed by a thermal reaction to convert at least a portion of the AxSi alloy into an oxide of metal A, and removing the oxide of metal A to obtain a silicon carbon composite material.

[0124] In the above technical means, according to the manufacturing method of the negative electrode material of the present application, a layer of silicon alloy AxSi is formed on the surface of the silicon-based material by alloying the silicon-based material with the active metal A, that is, a composite is obtained in which AxSi covers the silicon-based material, and the metal component in the silicon alloy AxSi in the composite has strong reducing properties at high temperatures, so that the composite and the carbon source can thermally react with each other to break and recombine the functional groups or chemical bonds in the carbon source to form a carbon material, and the silicon elements in the silicon alloy AxSi are inserted in situ into the carbon material in the form of silicon particles, and after removing the oxide of the metal A, a bulky and porous carbon matrix material is formed on the surface of the silicon-based material, and the silicon particles can be dispersed in the carbon matrix. The pores in the bulky carbon matrix can effectively relieve the volume expansion of the silicon-based material, and can be a flexible conductor, providing more transport paths for ions and electrons, strengthening the conductivity between the core and the outside, and improving the multiplication performance. The manufacturing method of the present application is simple and easy to implement, and effectively solves the problems of large volume expansion and low electrical conductivity of the negative electrode material, thereby improving the electrochemical properties of the battery containing the negative electrode material.

[0125] The production method of the present invention will be specifically described below with reference to examples.

[0126] In step S110, a composite is produced that includes a silicon-based material and an AxSi alloy (wherein A is an active metal and X=1 to 3) formed on at least a portion of the surface of the silicon-based material.

[0127] In some embodiments, step S110 includes alloying the silicon-based material with the active metal A in a protective atmosphere. As can be seen, after the alloying reaction, the surface portion of the silicon-based material reacts with the active metal A to form a layer of silicon alloy AxSi, and the silicon-based material located inside does not react, thereby obtaining a composite in which AxSi coats the silicon-based material.

[0128] In some embodiments, the molar ratio of the silicon-based material to the active metal A is 1:(0.1 to 3), specifically, it may be 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, etc. Of course, other values within the above range may also be used and are not limited here. By controlling the molar ratio of the silicon-based material to the active metal, the thickness of the silicon alloy AxSi can be controlled.

[0129] In some embodiments, the silicon-based material includes at least one of elemental silicon, silicon alloy, and silicon oxide.

[0130] In some embodiments, the silicon alloy includes at least one selected from silicon-tin alloy, silicon-lithium alloy, and silicon-germanium alloy.

[0131] In some embodiments, the silicon oxide is SiOx (0 < x ≤ 2), specifically, SiO 0.1 , SiO 0.2 , SiO 0.5 , SiO 0.8 , SiO 1.2 , SiO 1.5 , SiO 1.8 , SiO 1.9 or SiO 2.0 etc. may be used. The silicon oxide can react with the active metal A to generate a silicon alloy AXSi and an active metal oxide.

[0132] In some embodiments, the silicon-based material includes at least one of a particulate shape, a spherical shape, a substantially spherical shape, a linear shape, and a tubular shape. The silicon-based material of the present application can adopt various forms of silicon materials, with a simple process and high versatility.

[0133] In some embodiments, the silicon-based material has a spherical or substantially spherical shape.

[0134] In some embodiments, the median diameter of the silicon-based material is 0.1 μm to 15 μm, specifically, 0.1 μm, 0.2 μm, 0.3 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm, etc., and of course, other values ​​within the above range are also possible, and are not limited here.Preferably, the median diameter of the silicon-based material is 0.5 μm to 5 μm.

[0135] In some embodiments, the active metal A comprises at least one of Mg, Al, Ca, and Zn.

[0136] In some embodiments, the silicon-based material and the active metal A can be mixed before the alloying reaction between the silicon-based material and the active metal A. The mixing method may include magnetic stirring, mechanical stirring, ultrasonic dispersion, or abrasive dispersion.

[0137] In some embodiments, the alloying reaction may be, for example, vacuum sintering, hot press sintering, or pressureless sintering.

[0138] In some embodiments, the temperature of the alloying reaction is 400°C to 900°C, specifically, the temperature of the first heat treatment may be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, etc., and of course other values ​​within the above range are also possible and are not limited here.

[0139] In some embodiments, the incubation time for the alloying reaction is 1 h to 24 h, and may be, for example, 1 h, 3 h, 6 h, 10 h, 13 h, 15 h, 18 h, 20 h, 24 h, etc., and of course may be other values ​​within the above range and are not limited thereto.

[0140] In some embodiments, the heating rate of the alloying reaction is 1°C / min to 10°C / min, and may be, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc., and of course may be other values ​​within the above range and are not limited thereto.

[0141] In some embodiments, the thickness of the AxSi alloy formed on at least a part of the surface of the silicon-based material is 0.05 μm to 20 μm, specifically, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 17 μm, 20 μm, etc., and of course, other values ​​within the above range are also possible, and are not limited here.As can be understood, the thickness of the silicon alloy AxSi is mainly determined by the molar ratio of the silicon-based material and the active metal A.

[0142] In some embodiments, the median diameter of the complex is 0.1 μm to 20 μm, specifically, it may be 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, etc., and may of course be other values ​​within the above range, and is not limited here. It is preferably 0.5 μm to 10 μm, and more preferably 1 μm to 5 μm.

[0143] In some embodiments, the protective atmosphere comprises at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas.

[0144] In step S120, the composite and a carbon source are mixed together and then subjected to a thermal reaction to convert at least a part of the AxSi alloy into an oxide of metal A, and remove the oxide of metal A to obtain a silicon carbon composite material.

[0145] In some embodiments, the carbon source includes an organic carbon source, which is an aldehyde, a phenol, or a halogenated compound corresponding thereto that is solid under room temperature conditions and has a boiling point of less than 650° C. For example, the organic carbon source may be at least one of polyhydroxyaldehyde, hydroxybenzaldehyde, 2-bromo-5-hydroxybenzaldehyde, 2,6-dichlorophenol, and p-chlorophenol.

[0146] In some embodiments, the carbon source comprises an inorganic carbon source. The inorganic carbon source is a carbon-containing inorganic salt, including carbonates and bicarbonates. For example, the inorganic carbon source may be at least one of calcium carbonate, sodium carbonate, zinc carbonate, barium carbonate, sodium bicarbonate, and calcium bicarbonate.

[0147] In some embodiments, step S120 is performed in a protective atmosphere, the protective atmosphere including at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas.

[0148] In some embodiments, the carbon matrix includes a solid portion and voids distributed in the solid portion, with some of the silicon particles dispersed in the voids and some of the silicon particles embedded in the solid portion.

[0149] As can be seen, some of the silicon particles obtained by reduction are inserted into the solid part of the carbon matrix and completely wrapped by carbon, which improves the electrical conductivity of the silicon particles, improves the multiplication performance of the negative electrode material, and can meet the requirement of realizing the fast charging characteristics of the battery; another part of the silicon particles is inserted into the pores of the carbon matrix, and the silicon particles are not completely filled, leaving enough space to ease the volume expansion of the silicon particles, thereby avoiding the destruction of the entire material due to the volume expansion, and at the same time reducing the expansion of the electrode film and improving the safety of the battery.

[0150] By controlling the ratio of the AxSi alloy and the carbon source, the molar ratio of the silicon particles embedded in the solid part and the silicon particles dispersed in the pores can be controlled. The pores filled with silicon particles are mainly left after pickling the oxide of metal A. When the carbon source is sufficient, it can be guaranteed that metal A and the carbon source are completely reacted, and at this time, the silicon particles are all dispersed in the pores. When the carbon source is insufficient, a part of the AxSi alloy reacts with the carbon source to generate nanosilicon particles dispersed in the pores, and the remaining AxSi alloy is decomposed into A (vapor form) and silicon particles in the carbon layer, and these silicon particles are embedded in the solid part. Thus, by controlling the amount of the carbon source, the content of silicon particles at two different positions in the carbon matrix can be adjusted, and the demand for high-magnification and low-expansion silicon-carbon composite products can be met.

[0151] In some embodiments, the carbon matrix is ​​an amorphous porous carbon material.

[0152] In some embodiments, removing the oxide of metal A in the thermal reaction product comprises pickling the thermal reaction product with an acid solution. Specifically, the thermal reaction product includes carbon, elemental silicon, and active oxide of metal A, and the active oxide of metal A can be removed by an acid solution treatment.

[0153] In some embodiments, the thermal reaction product may be treated in an acid solution having a concentration of 1 mol / L to 5 mol / L for 1 h to 10 h.

[0154] In some embodiments, the acid solution comprises at least one of hydrochloric acid, nitric acid, and sulfuric acid.

[0155] In some embodiments, the concentration of the acid solution may be specifically 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, etc., and of course may be other values ​​within the above range, and is not limited thereto.

[0156] In some embodiments, the time of treatment with the acid solution may be specifically 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc., and of course may be other values ​​within the above ranges and are not limited thereto.

[0157] In some embodiments, the molar ratio of the composite to the carbon source is 1: (0.01-10), specifically, it may be 1:0.01, 1:0.1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., and of course, it may be other values ​​within the above range, and is not limited here. As can be understood, the present invention changes the size and porosity of the pores in the carbon matrix by controlling the molar ratio of the composite material M to the carbon source, i.e., by controlling the molar ratio of the silicon alloy AxSi to the carbon source. Specifically, the metal A in the silicon alloy AxSi reacts with the oxygen in the carbon source to produce metal oxide, and the carbon source is carbonized into a carbon matrix during the thermal reaction process, and the metal oxide is removed by pickling, leaving vacancies in the carbon matrix, forming a carbon matrix with vacancies. The higher the silicon content in the silicon alloy AxSi, the smaller the metal content and the smaller the pore size of the vacancies. The higher the silicon content in the silicon alloy AxSi, the thicker the silicon alloy and the thicker the carbon matrix formed, which can play a good conductive role for silicon particles in a larger size range.

[0158] In some embodiments, the mixing method may include magnetic stirring, mechanical stirring, ultrasonic dispersion, or abrasive dispersion.

[0159] In some embodiments, the temperature of the thermal reaction is between 200°C and 950°C, and may be, for example, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 950°C, etc., and of course may be other values ​​within the above range, and is not limited thereto.

[0160] In some embodiments, the incubation time for the thermal reaction is 1 h to 24 h, for example, the incubation time may be 1 h, 3 h, 6 h, 10 h, 13 h, 15 h, 18 h, 20 h, 24 h, etc., and of course other values ​​within the above ranges are also possible and are not limited thereto.

[0161] In some embodiments, the heating rate of the thermal reaction is 1° C. / min to 20° C. / min, and may be, for example, 1° C. / min, 2° C. / min, 3° C. / min, 4° C. / min, 5° C. / min, 6° C. / min, 7° C. / min, 8° C. / min, 9° C. / min, 10° C. / min, 11° C. / min, 12° C. / min, 13° C. / min, 14° C. / min, 15° C. / min, 16° C. / min, 17° C. / min, 18° C. / min, 19° C. / min, 20° C. / min, etc., and of course may be other values ​​within the above range and are not limited thereto.

[0162] The manufacturing method of the present application further includes a step S130 of forming a coating layer on the surface of the silicon carbon composite material to obtain a negative electrode material.

[0163] In the above technical means, a coating treatment is performed on the surface of the silicon-carbon composite material, and a carbon substrate and a coating layer are provided on the surface of the silicon-based material, which in turn coat the bulky silicon particles. The formation of the coating layer can effectively solve the problem that the silicon negative electrode has a large volume expansion and low conductivity.

[0164] In some embodiments, the step of forming a cover layer may be omitted.

[0165] In some embodiments, step S130 includes sintering the mixture including the silicon carbon composite and the polymer particles under vacuum conditions to form the coating layer.

[0166] In the above technical means, polymer particles can be directly used to coat the negative electrode material, thereby realizing the surface coating of the negative electrode material. On the one hand, the coating process with polymer can avoid the electrolyte entering the inside of the negative electrode material and causing side reactions, which reduces the initial efficiency and capacity; on the other hand, it can cooperate with the amorphous carbon matrix to ease the volume expansion of silicon, reduce the volume expansion of the entire composite material, and reduce the swelling of the electrode strip.

[0167] In some embodiments, the polymer particles include at least one of asphalt, resin, polyester-based polymer, polyamide-based polymer.

[0168] In some embodiments, the mass ratio of the polymer particles to the silicon carbon composite is 1: (0.1-10), specifically, the mass ratio of the polymer particles to the silicon carbon composite is 1:0.1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 and 1:10, etc., and of course, it can be other values ​​within the above range, and is not limited here. Controlling the mass ratio of the polymer particles to the silicon carbon composite within the above range is helpful to improve the initial efficiency.

[0169] In some embodiments, the sintering temperature is between 600°C and 1000°C, and may be, for example, 600°C, 700°C, 800°C, 900°C, 1000°C, etc., and of course other values ​​within the above ranges, and are not limited thereto.

[0170] In some embodiments, the sintering incubation time is 1 h to 24 h, and may be, for example, 1 h, 3 h, 6 h, 10 h, 13 h, 15 h, 18 h, 20 h, 24 h, etc., and of course may be other values ​​within the above range and are not limited thereto.

[0171] In some embodiments, the sintering heating rate is 1° C. / min to 20° C. / min, and may be, for example, 1° C. / min, 2° C. / min, 3° C. / min, 4° C. / min, 5° C. / min, 6° C. / min, 7° C. / min, 8° C. / min, 9° C. / min, 10° C. / min, 11° C. / min, 12° C. / min, 13° C. / min, 14° C. / min, 15° C. / min, 16° C. / min, 17° C. / min, 18° C. / min, 19° C. / min, 20° C. / min, etc., and of course may be other values ​​within the above range and are not limited thereto.

[0172] In some embodiments, the degree of vacuum under the vacuum condition is less than 0.1 Mpa, specifically, the degree of vacuum may be 0.05 Mpa, 0.06 Mpa, 0.07 Mpa, 0.08 Mpa, and 0.09 Mpa, and of course, may be other values ​​within the above range, and is not limited thereto.

[0173] In some embodiments, step S130 includes synthesizing a polymer on the surface of the silicon carbon composite material using a chemical synthesis method to form a coating layer.

[0174] In some embodiments, the chemical synthesis method comprises a polymerization reaction, wherein the monomers participating in the polymerization reaction comprise at least one of dopamine, tannic acid, phenolic resin, glucose, starch, melamine, urethane, and acrylic acid.

[0175] In some embodiments, the coating layer includes a polymer, and the polymer includes at least one of a resin-based polymer and a polyester-based polymer. For example, the resin-based polymer may be any one of an epoxy resin, an acrylic resin, a polyester resin, an amino resin, and a phenolic resin, and the polyester-based polymer may be any one of a polyurethane, a thermosetting polyester, and a thermoplastic polyester.

[0176] In some embodiments, step S130 includes forming a coating layer on the surface of the silicon carbon composite material by chemical vapor deposition of an organic carbon source.

[0177] In a third aspect, the present application provides a lithium ion battery comprising the above-described negative electrode material.

[0178] The present invention will be further described below by dividing it into several embodiments. However, the present invention is not limited to the following specific embodiments. The present invention may be modified as appropriate without changing the scope of the main claims.

[0179] Example 1 (1) Silicon powder with a median diameter of 1 μm and magnesium powder are mixed uniformly in a molar ratio of 1:0.5, then placed in an atmospheric furnace, heated to 600°C at a heating rate of 3°C / min, and then kept at that temperature for 6 hours. After they are sufficiently alloyed, a composite is obtained in which a silicon-magnesium alloy layer covers the silicon particles. (2) 1 mol of the composite and 1 mol of p-chlorophenol are mixed uniformly, and the mixture is placed in a sealed stainless steel reactor filled with an argon gas atmosphere. The reactor is heated to 750°C at a heating rate of 3°C / min and then kept at that temperature for 8 hours to fully react them to obtain a reaction product. The reaction product is mechanically stirred in a 1 mol / L hydrochloric acid solution for 2 hours, and then suction filtered, washed and dried to obtain a silicon-carbon composite material in which a porous silicon-carbon composite layer covers a silicon-based material. (3) After uniformly mixing the phenolic resin and silicon carbon composite material in a mass ratio of 1:5, the mixture is placed in a vacuum reactor with a vacuum degree of 0.05Mpa. The reactor is then heated to 1000°C at a heating rate of 3°C / min and kept at that temperature for 6 hours to fully react them and obtain the negative electrode material.

[0180] FIG. 5 is a scanning electron microscope photograph of the negative electrode material in this Example 1. As shown in the scanning electron microscope photograph of FIG. 5, the surface of the produced negative electrode material is a single dense carbon coating layer.

[0181] FIG. 6 is the Raman spectrum of the negative electrode material in this Example 1. As shown in the Raman imaging of FIG. 6, it further proves that there is one D peak and one G peak near 1350 cm-1 and 1580 cm-1, which are characteristic peaks of amorphous carbon.

[0182] FIG. 7 is an XRD chart of the negative electrode material in this Example 1. As shown in the XRD pattern in FIG. 7, the three strong peaks at 28.4°, 47.3° and 56.1° respectively correspond to the three strong peaks of silicon (JCPDS No. 27-1402), and there is essentially no heterophase.

[0183] Fig. 8 is a cycle characteristic curve diagram of the negative electrode material in this Example 1, where the charge / discharge current is 1000mA / g. As shown in Fig. 8, the material has excellent cycle performance, with a remaining capacity of 725mAh / g after 820 cycles at a high current of 1000mA / g.

[0184] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on a surface of the core, the core includes elemental silicon, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is a carbon coating layer.

[0185] Example 2 (1) Silicon powder with a median diameter of 3 μm and magnesium powder are mixed uniformly in a molar ratio of 1:0.1, then placed in an atmospheric furnace, heated to 650°C at a heating rate of 1°C / min, and then kept at that temperature for 6 hours. After they are sufficiently alloyed, a composite is obtained in which a silicon-magnesium alloy layer covers the silicon particles. (2) 1 mol of the composite and 5 mol of calcium carbonate are mixed uniformly, and the mixture is placed in a sealed stainless steel reactor filled with a nitrogen gas atmosphere. The reactor is heated to 800°C at a heating rate of 7°C / min and then kept at that temperature for 1 hour to fully react them to obtain a reaction product. The reaction product is mechanically stirred in a 1 mol / L sulfuric acid solution for 2 hours, and then suction filtered, washed and dried to obtain a silicon carbon composite material. (3) The polyamide and silicon carbon composite material N are uniformly mixed in a mass ratio of 1:10, then placed in a vacuum reactor with a vacuum degree of 0.01 MPa. The reactor is then heated to 1000°C at a heating rate of 3°C / min and kept at that temperature for 6 hours to fully react with each other and obtain the negative electrode material.

[0186] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on a surface of the core, the core includes elemental silicon, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is a carbon coating layer.

[0187] Example 3 (1) Silicon powder with a median diameter of 8 μm and magnesium powder are mixed uniformly in a molar ratio of 1:1.5, then placed in a nitrogen gas atmosphere furnace, heated to 750°C at a heating rate of 5°C / min, and then kept at that temperature for 2 hours to fully alloy them, resulting in a composite in which a silicon-magnesium alloy layer covers the silicon particles. (2) 1 mol of the composite and 0.1 mol of calcium carbonate are mixed uniformly, and the mixture obtained is placed in a sealed stainless steel reaction kettle filled with a krypton gas atmosphere. The reaction kettle is heated to 500°C at a heating rate of 5°C / min and then kept at that temperature for 6 hours to fully react them to obtain a reaction product. The reaction product is mechanically stirred in a 1 mol / L hydrochloric acid solution for 2 hours, and then suction filtered, washed and dried to obtain a silicon-carbon composite material in which a porous silicon-carbon composite layer covers a silicon-based material. (3) The pitch and silicon carbon composite material are uniformly mixed in a mass ratio of 2:5, then placed in a vacuum reactor with a vacuum degree of 0.01 MPa. The reactor is then heated to 900°C at a heating rate of 15°C / min and kept at that temperature for 1 hour to fully react with each other and obtain the negative electrode material.

[0188] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on the surface of the core, the core includes elemental silicon, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is an amorphous carbon coating layer.

[0189] Example 4 (1) Silicon powder with a median diameter of 15 μm and zinc powder are mixed uniformly in a molar ratio of 1:3, then placed in a neon gas atmosphere furnace, heated to 500°C at a heating rate of 20°C / min, and then kept at that temperature for 24 hours. After they are sufficiently alloyed, a composite is obtained in which a silicon-magnesium alloy layer covers the silicon particles. (2) 1 mol of the composite and 10 mol of sodium carbonate are mixed uniformly, and the mixture is placed in a sealed stainless steel reactor filled with a neon gas atmosphere. The reactor is heated to 900°C at a heating rate of 5°C / min and then kept at that temperature for 15 hours to fully react them to obtain a reaction product. The reaction product is mechanically stirred in a 1 mol / L nitric acid solution for 2 hours, and then suction filtered, washed and dried to obtain a silicon-carbon composite material in which a porous silicon-carbon composite layer covers a silicon-based material. (3) After uniformly mixing the phenolic resin and silicon carbon composite material in a mass ratio of 1:0.1, the mixture is placed in a vacuum reactor with a vacuum degree of 0.01 MPa. The reactor is then heated to 950°C at a heating rate of 20°C / min and kept at that temperature for 6 hours to fully react them and obtain the negative electrode material.

[0190] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on the surface of the core, the core includes elemental silicon, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is an amorphous carbon coating layer.

[0191] Example 5 (1) Silicon powder with a median diameter of 0.2 μm and magnesium powder are mixed uniformly in a molar ratio of 1:2, then placed in a nitrogen gas atmosphere furnace, heated to 900°C at a heating rate of 10°C / min, and then kept at that temperature for 1 hour. After they are sufficiently alloyed, a composite is obtained in which a silicon-magnesium alloy layer covers the silicon particles. (2) 1 mol of the complex and 0.01 mol of hydroxybenzaldehyde are mixed uniformly, and the mixture is placed in a sealed stainless steel reaction kettle filled with argon gas atmosphere. The reaction kettle is heated to 750°C at a heating rate of 15°C / min and then kept at that temperature for 8 hours to fully react them to obtain a reaction product. The reaction product is mechanically stirred in a 1 mol / L hydrochloric acid solution for 2 hours, and then suction filtered, washed and dried to obtain a silicon carbon composite material in which a porous silicon carbon layer covers a silicon-based material. (3) After uniformly mixing the phenolic resin and silicon carbon composite material in a mass ratio of 1:8, the mixture is placed in a vacuum reactor with a vacuum degree of 0.05 MPa. The reactor is then heated to 1000°C at a heating rate of 20°C / min and kept at that temperature for 10 hours to fully react them and obtain the negative electrode material.

[0192] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on the surface of the core, the core includes elemental silicon, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is an amorphous carbon coating layer.

[0193] Example 6 (1) Silicon powder with a median diameter of 5 μm and aluminum powder are mixed uniformly in a molar ratio of 1:0.1, then placed in an argon gas atmosphere furnace, heated to 900°C at a heating rate of 5°C / min, and kept at that temperature for 1 hour to fully alloy them, resulting in a composite in which a silicon-aluminum alloy layer covers the silicon particles. (2) 1 mol of the composite and 5 mol of hydroxybenzaldehyde are mixed uniformly, and the mixture is placed in a sealed stainless steel reaction kettle filled with a helium gas atmosphere. The reaction kettle is heated to 950°C at a heating rate of 10°C / min, and then kept at that temperature for 10 hours to fully react them to obtain a reaction product. The reaction product is mechanically stirred in a 1 mol / L nitric acid solution for 2 hours, and then suction filtered, washed and dried to obtain a silicon-carbon composite material in which a porous silicon-carbon composite layer covers a silicon-based material. (3) 1 kg of silicon carbon composite material is dispersed in 10 L of deionized water, 200 ml of ammonia solution is added and stirred uniformly, then 1 kg of resorcinol and 100 ml of formaldehyde solution are added, stirred at room temperature for 8 hours, and then centrifuged and dried. The dried product is heated to 950°C at a heating rate of 3°C / min in a reactor, and then kept at that temperature for 6 hours to fully react with each other to obtain a negative electrode material.

[0194] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on the surface of the core, the core includes elemental silicon, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is a phenolic resin coating layer.

[0195] Example 7 A negative electrode material is obtained in the same manner as in Example 1, except that the step (3) is not carried out.

[0196] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on the surface of the core, the core includes elemental silicon, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, and the carbon matrix has pores.

[0197] Example 8 In step (3), a negative electrode material is obtained in the same manner as in Example 1, except that titanium oxide is used instead of the phenol resin.

[0198] The negative electrode material produced in this example has a core-shell structure, and includes a core and a porous silicon carbon composite layer distributed on the surface of the core, the core including elemental silicon, the porous silicon carbon composite layer including a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix having pores, and the coating layer being a titanium oxide coating layer.

[0199] Example 9 In step (3), a negative electrode material is obtained in the same manner as in Example 1, except that titanium nitride is used instead of the phenolic resin.

[0200] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on the surface of the core, the core includes elemental silicon, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is a titanium nitride coating layer.

[0201] Example 10 (1) Silicon germanium alloy powder with a median diameter of 1 μm and magnesium powder are mixed uniformly in a molar ratio of 1:0.4, then placed in an atmospheric furnace, heated to 600°C at a heating rate of 3°C / min, and then kept at that temperature for 6 hours to fully alloy them, obtaining a composite in which a silicon-magnesium alloy layer covers the silicon germanium alloy particles. (2) 1 mol of the composite and 1 mol of p-chlorophenol are mixed uniformly, and the mixture is placed in a sealed stainless steel reactor filled with an argon gas atmosphere. The reactor is heated to 750°C at a heating rate of 3°C / min and then kept at that temperature for 8 hours to fully react them to obtain a reaction product. The reaction product is mechanically stirred in a 1 mol / L hydrochloric acid solution for 2 hours, and then suction filtered, washed and dried to obtain a silicon-carbon composite material in which a porous silicon-carbon composite layer covers a silicon-based material. (3) After uniformly mixing the phenolic resin and silicon carbon composite material in a mass ratio of 1:5, the mixture is placed in a vacuum reactor with a vacuum degree of 0.05Mpa. The reactor is then heated to 1000°C at a heating rate of 3°C / min and kept at that temperature for 6 hours to fully react them and obtain the negative electrode material.

[0202] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on a surface of the core, the core includes a silicon germanium alloy, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is an amorphous carbon coating layer.

[0203] Example 11 (1) Silicon oxide (SiO) powder with a median diameter of 3 μm and magnesium powder are mixed uniformly in a molar ratio of 1:0.8, then placed in an atmospheric furnace, heated to 650°C at a heating rate of 1°C / min, and then kept at that temperature for 6 hours. After they are sufficiently alloyed, a composite is obtained in which a silicon-magnesium alloy layer covers the silicon oxide particles. (2) 1 mol of the composite and 5 mol of calcium carbonate are mixed uniformly, and the mixture is placed in a sealed stainless steel reactor filled with a nitrogen gas atmosphere. The reactor is heated to 800°C at a heating rate of 7°C / min and then kept at that temperature for 1 hour to fully react them to obtain a reaction product. The reaction product is mechanically stirred in a 1 mol / L sulfuric acid solution for 2 hours, and then suction filtered, washed and dried to obtain a silicon carbon composite material. (3) The polyamide and silicon carbon composite material N are uniformly mixed in a mass ratio of 1:10, then placed in a vacuum reactor with a vacuum degree of 0.01 MPa. The reactor is then heated to 1000°C at a heating rate of 3°C / min and kept at that temperature for 6 hours to fully react with each other and obtain the negative electrode material.

[0204] The negative electrode material produced in this example has a core-shell structure, and the negative electrode material includes a core and a porous silicon carbon composite layer distributed on a surface of the core, the core includes silicon oxide, the porous silicon carbon composite layer includes a carbon matrix and silicon particles dispersed in the carbon matrix, the carbon matrix has pores, and the coating layer is a carbon coating layer.

[0205] Comparative Example 1 Unlike Example 1, a carbon coating layer is directly formed on the surface of the core, and the specific manufacturing process is as follows.

[0206] The silicon-based material and the phenolic resin are mixed uniformly in a mass ratio of 5:1, then placed in a vacuum reactor with a vacuum degree of 0.05 MPa. The reactor is then heated to 900°C at a heating rate of 3°C / min, and then kept at that temperature for 6 hours to fully react them and obtain the negative electrode material.

[0207] <Performance test> 1. Mass content of silicon particles in the negative electrode material: A focused ion beam (FIB) is used to peel off the surface of the negative electrode material layer by layer, and a scanning electron microscope (SEM) and an electronic dosimeter (EDS) are combined to measure the silicon element content in the composite layer of each cross section, and the silicon particle content of each cross section is calculated by statistically calculating the total mass of silicon particles in the composite layer. "Total mass of silicon particles / mass of negative electrode material" is the mass content of silicon particles in the negative electrode material.

[0208] 2. Mass content of silicon-based material core in negative electrode material: A focused ion beam (FIB) is used to peel off the composite negative electrode material particles layer by layer, and a scanning electron microscope (SEM) and an energy dispersing spectrometer (EDS) are combined to measure the elemental content of the silicon-based material core in each cross section (the silicon elemental content is measured in the simple silicon core, the silicon and metal elemental content is measured in the silicon alloy core, and the silicon and oxygen elemental content is measured in the silicon oxide core), and the total elemental content of the silicon-based material core in each cross section is statistically calculated to obtain the mass content of the silicon-based material core in the negative electrode material.

[0209] 3. The mass content of the carbon material in the negative electrode material: the thermogravimetric curve of the carbon material is measured by TG / DSC test, and the TG curve is combined according to the exothermic peak position to obtain the mass content of the carbon material.

[0210] 4. Ratio of pore volume between macropores and mesopores: The ratio of pore volume between macropores and mesopores is obtained by the BET-BJH test.

[0211] 5. Porosity of the negative electrode material: The porosity of the negative electrode material is measured using a mercury intrusion tester.

[0212] 6. Tap density of the powder of the negative electrode material: Obtained by direct measurement using a powder tap density tester.

[0213] 7. Mass ratio of silicon particles to silicon-based material: The silicon particle content is obtained by Measurement Method 1, and the silicon-based material content is obtained by Measurement Method 2.

[0214] 8. Median diameter of silicon particles: A focused ion beam (FIB) is used to perform cross-sectional peeling of 10 negative electrode material particles, one layer at a time, and a scanning electron microscope (SEM) and an electronic data spectroscope (EDS) are combined to measure the size of the silicon particles in each cross section. The measured silicon particle sizes are compiled as statistics, and the size of irregular silicon particles is calculated as the average value of the maximum length and maximum width of the cross section. The particle diameter at which the cumulative particle size distribution percentage reaches 50% is the median diameter.

[0215] 9. Median diameter of silicon-based material: A focused ion beam (FIB) is used to perform cross-sectional peeling of 10 composite negative electrode material particles, one layer at a time, and a scanning electron microscope (SEM) and an electronic data spectroscope (EDS) are combined to measure the size of the silicon-based material on each cross-section. The size of the irregular silicon-based material is calculated as the average value of the maximum length and maximum width of the cross-section. The measured silicon-based material sizes are statistically collected. The particle diameter at which the cumulative particle size distribution percentage reaches 50% is the median diameter.

[0216] 10. Thickness of the porous silicon carbon composite layer: Scanning electron microscopy characterization is performed with a transmission electron microscope at an operating voltage of 200 kV to measure the thickness of the porous silicon carbon composite layer with a scale.

[0217] 11. In a porous silicon carbon composite layer, the molar ratio of silicon particles distributed in the solid part and silicon particles dispersed in the pores: A focused ion beam (FIB) is used to perform cross-sectional peeling of the negative electrode material particles one layer at a time, and a scanning electron microscope (SEM) and an electron dosimeter (EDS) are used in combination to analyze the elemental content of the silicon particles in the solid part and the silicon particles distributed in the pores, and the ratio of the silicon particle content at the two positions is statistically calculated, i.e., the molar ratio is obtained.

[0218] 12. Median diameter of negative electrode material: Using a laser particle size analyzer Malvern MS3000, the negative electrode material is measured, and the particle size at which the volume percentage of the cumulative particle size distribution reaches 50% is calculated, that is, the median diameter is obtained.

[0219] 13. Specific surface area of ​​negative electrode material: measured using a US Micromeritics TriStar3020 specific surface tester.

[0220] 14. Oxygen content of negative electrode material: Oxygen, nitrogen and hydrogen analyzer from VERDER, Germany (ELTRA ONH 2000) is used for measurement.

[0221] 15. The resilience is measured using the following method. The resilience is measured by combining an in-situ transmission electron microscope (TEM) and an electrochemical measurement system. The resilience is obtained by measuring the thickness of the porous silicon carbon composite layer after compression and the thickness after rebound using an in-situ transmission electron microscope. After applying a voltage to the negative electrode material, the silicon-based material core expands to press the porous silicon carbon composite layer, and the thickness after compression is He. After applying a reverse voltage, the silicon-based material core contracts and the porous silicon carbon composite layer begins to rebound, where the rebound thickness is Hd and the original thickness of the porous silicon carbon composite layer is Hi. Compressibility=(Hi-He) / Hi*100%, resilience=Hd / (Hi-He)*100%.

[0222] 16. Measure the electrochemical cycling performance using the following method. The negative electrode material, conductive agent and adhesive prepared in Examples 1-11 and Comparative Example 1 are dissolved and mixed in a solvent in a mass ratio of 94:1:5, the solid content is controlled to 50%, coated on a copper foil current collector, and vacuum dried to prepare a negative electrode piece. Then, the ternary positive electrode piece prepared by the conventional maturation process, 1mol / L LiPF6 / ethyl cellulose+dimethyl carbonate+ethyl methyl carbonate (v / v / v=1:1:1) electrolyte, polypropylene separator (Celgard 2400) and housing are assembled into a 18650 cylindrical single battery by a normal manufacturing process. The charge and discharge current is set to a constant current of 0.2C and the charge and discharge voltage is limited to 2.75-4.2V under normal temperature conditions by the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd., and the charge and discharge test of the cylindrical battery is performed to obtain the initial reversible capacity, the initial charge capacity and the initial discharge capacity. Initial coulombic efficiency = Initial discharge capacity / Initial charge capacity After repeating 50 cycles, the thickness of the lithium ion battery pole piece at this time is measured as H1 using a micrometer, and the initial thickness of the battery pole piece is measured as H0. Expansion rate after 50 cycles = ((H1-H0) / H0) x 100% The battery was cycled 100 times, and the discharge capacity was recorded as the remaining capacity of the lithium-ion battery. Capacity maintenance rate = (remaining capacity / initial capacity) x 100%

[0223] The results of the above performance tests are shown in Table 1. The negative electrode materials produced in Examples 1 to 11 and Comparative Example 1 were used in lithium ion batteries and were numbered S1, S2, S3, S4, S5, S6, S7, S8 and S9, respectively, and the number corresponding to Comparative Example 1 was Ref-1.

[0224] [Table 1]

[0225] As is clear from Table 1, the negative electrode materials produced in Examples 1 to 5 include a silicon-based material core, a porous silicon-carbon composite layer, and a coating layer, and the pores of the porous silicon-carbon composite layer can effectively mitigate the volume expansion of the core and silicon particles, and can be flexible conductors, provide more transport paths for ions and electrons, strengthen the conductivity between the core and the outside, and improve the multiplication performance. On the one hand, the installation of the coating layer can avoid the reduction in initial efficiency and capacity caused by the electrolyte entering the inside and causing side reactions, and on the other hand, it can cooperate with the porous silicon-carbon composite layer to mitigate the volume expansion of the core and silicon particles, reduce the volume expansion of the entire negative electrode material, and reduce the swelling of the electrode sheet. The negative electrode material produced by the present invention exhibits advantages such as high capacity, high rate characteristics, and low expansion, and can be widely applied in the field of negative electrodes of high-performance lithium-ion batteries.

[0226] In Example 6, a chemical synthesis method is used to coat a polymer on the surface of a silicon carbon composite material to obtain a coating layer. The resulting negative electrode material also exhibits the characteristics of low volume expansion and high capacity.

[0227] In Example 7, in the manufacturing process of the negative electrode material, a coating layer was not manufactured, and the contact between silicon and the electrolyte could not be reduced, and the mitigation of volume expansion was limited. As a result, the expansion rate of the electrode film was large, and the discharge specific capacity of the negative electrode material was low.

[0228] In Examples 8 and 9, a metal oxide layer and a metal nitride layer were respectively prepared on the surface of the silicon carbon composite material, and the resulting negative electrode materials also exhibited excellent electrochemical properties.

[0229] In Examples 10 and 11, silicon germanium alloy is respectively adopted as the core material, and the obtained negative electrode material can exhibit the characteristics of low volume expansion and high capacity.

[0230] In Example 11, silicon oxide (SiO) was used as the core material, and the obtained negative electrode material also exhibited excellent suppression performance of volume expansion, and the capacity retention rate could be maintained at a high level.

[0231] In Comparative Example 1, the porous silicon-carbon composite layer was not produced during the production process of the negative electrode material, and the volume expansion of silicon was large after absorbing lithium, which resulted in the material being powdered, the capacity of the negative electrode material being low, and the expansion rate of the electrode film being large.

[0232] The present application describes the detailed process equipment and process flow of the present application through the above embodiment, but the applicant declares that the present application is not limited to the above detailed process equipment and process flow, that is, the present application is not limited to the above detailed process equipment and process flow. As is obvious to those skilled in the art, any improvements to the present application, such as equivalent replacement of each raw material of the product of the present application, addition of auxiliary components, selection of specific methods, etc., are all within the scope of the claims and disclosure of the present application. [Explanation of symbols]

[0233] 1-Silicon-based materials 2-Porous silicon-carbon composite layer 21-Carbon Matrix 22-Vacancy 23-Silicon particles 3-Coating layer

Claims

1. a core; and a porous silicon carbon composite layer distributed on at least a portion of a surface of the core; the core is a silicon-based material; The silicon-based material is at least one of silicon, a silicon alloy, and a silicon oxide; The porous silicon carbon composite layer comprises a carbon matrix having pores and silicon particles dispersed in the carbon matrix; 13. A negative electrode material, comprising: a porous silicon carbon composite layer having a resilience of 90% or more when the porous silicon carbon composite layer has a compressibility of 50%.

2. 2. The negative electrode material according to claim 1, wherein at least a portion of the silicon particles are dispersed in the pores of the carbon matrix.

3. The negative electrode material according to claim 1 or 2, which satisfies at least one of the following (1) to (17): (1) The silicon alloy includes at least one selected from a silicon-tin alloy, a silicon-lithium alloy, and a silicon-germanium alloy; (2) The silicon oxide is SiOx (0<x≦2); (3) The silicon-based material has at least one of a particulate shape, a spherical shape, a substantially spherical shape, a linear shape, and a tubular shape; (4) The silicon-based material has a median diameter of 0.1 μm to 15 μm; (5) The silicon-based material has a median diameter of 1 μm to 5 μm; (6) the porous silicon carbon composite layer has a thickness of 0.01 μm to 10 μm; (7) The ratio of the median diameter of the silicon-based material to the thickness of the porous silicon carbon composite layer is (1-10):1; (8) The negative electrode material has a porosity of 10% to 50%; (9) The content of the carbon matrix in the porous silicon carbon composite layer is 5% by mass to 80% by mass; (10) The pores include macropores and mesopores; (11) The pores include macropores and mesopores, and the ratio of the pore volume of the macropores to the pore volume of the mesopores is (0.5 to 5):1; (12) The silicon particles have a median diameter of 1 nm to 500 nm; (13) The silicon particles have a median diameter of 10 nm to 100 nm; (14) The mass ratio of the silicon particles to the silicon-based material is (0.3-0.7):1; (15) The carbon matrix includes a solid portion and voids distributed in the solid portion, and at least a portion of the silicon particles is embedded in the solid portion; (16) The carbon matrix includes a solid portion and voids distributed in the solid portion, and some of the silicon particles are dispersed in the voids and some of the silicon particles are embedded in the solid portion; (17) The carbon matrix includes a solid portion and voids distributed in the solid portion, some of the silicon particles are dispersed in the voids and some of the silicon particles are embedded in the solid portion, and the molar ratio of the silicon particles embedded in the solid portion to the silicon particles dispersed in the voids is 1:(0.5 to 3).

4. 2. The negative electrode material according to claim 1, further comprising a coating layer formed on at least a portion of a surface of the porous silicon carbon composite layer.

5. The negative electrode material according to claim 4, wherein the coating layer satisfies at least one of the following (1) to (7). (1) The coating layer includes at least one of a carbon material, a metal oxide, a nitride, and a conductive polymer; (2) The coating layer includes a carbon material, and the carbon material includes at least one of graphene, soft carbon, hard carbon, and amorphous carbon; (3) The coating layer includes a metal oxide, and the metal oxide includes at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide; (4) the coating layer includes a nitride, the nitride including at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride, and carbon nitride; (5) The coating layer includes a conductive polymer, and the conductive polymer includes at least one of polyaniline, polyacetylene, polypyrrole, polythiophene, poly(3-hexylthiophene-2,5-diyl), polyparaphenylenevinylene, polypyridine, and polyphenylenevinylene; (6) The coating layer has a thickness of 3 nm to 200 nm; (7) The coating layer has a porosity of 2% to 10%.

6. The negative electrode material according to claim 1 or 2, which satisfies at least one of the following (1) to (4): (1) The negative electrode material has a median particle size of 0.1 μm to 20 μm; (2) The negative electrode material has a specific surface area of ​​1.0 m 2 / g to 50m 2 / g; (3) The negative electrode material has a powder tap density of 0.2 g / m 3 ~1.2g / m 3 It is. (4) The negative electrode material has an oxygen content of less than 20 mass %.

7. A step of producing a composite including a silicon-based material and an AxSi alloy (wherein A is an active metal and X=1 to 3) formed on at least a portion of a surface of the silicon-based material; and mixing the composite with a carbon source and then carrying out a thermal reaction to convert at least a portion of the AxSi alloy into an oxide of metal A, and removing the oxide of metal A to obtain a silicon carbon composite material.

2. The method for producing a negative electrode material according to claim 1, wherein the silicon-based material is at least one of silicon, a silicon alloy, and a silicon oxide.

8. The method according to claim 7, characterized in that at least one of the following (1) to (25) is satisfied: (1) The silicon alloy includes at least one selected from a silicon-tin alloy, a silicon-lithium alloy, and a silicon-germanium alloy; (2) The silicon oxide is SiOx (0<x≦2); (3) The silicon-based material has at least one of a particulate shape, a spherical shape, a substantially spherical shape, a linear shape, and a tubular shape; (4) The silicon-based material is spherical or nearly spherical in shape; (5) The silicon-based material has a median diameter of 0.1 μm to 15 μm; (6) The silicon-based material has a median diameter of 1 μm to 5 μm; (7) The active metal A includes at least one of Mg, Al, Ca, and Zn; (8) The molar ratio of the silicon-based material to the active metal A is 1:(0.1-3); (9) The step of producing the composite includes alloying a silicon-based material with an active metal A in a protective atmosphere; (10) The step of preparing the composite includes alloying the silicon-based material with the active metal A in a protective atmosphere, wherein the alloying reaction is carried out at a temperature of 400°C to 900°C and for a holding time of 1 hour to 24 hours; (11) The step of producing the composite includes alloying a silicon-based material with an active metal A in a protective atmosphere, wherein the alloying reaction has a heating rate of 1° C. / min to 10° C. / min; (12) The step of producing the composite includes alloying the silicon-based material with the active metal A in a protective atmosphere, wherein the protective atmosphere includes at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas; (13) The AxSi alloy formed on at least a portion of the surface of the silicon-based material has a thickness of 0.05 μm to 20 μm; (14) The complex has a median diameter of 0.1 μm to 20 μm; (15) The carbon source comprises an organic carbon source; (16) The carbon source includes an organic carbon source, which is solid under room temperature conditions and includes at least one of aldehydes, phenols, and corresponding halogenated compounds, each of which has a boiling point of less than 650° C.; (17) The carbon source comprises an inorganic carbon source; (18) The carbon source comprises an inorganic carbon source, and the inorganic carbon source comprises a carbon-containing inorganic salt; (19) The thermal reaction after mixing the composite and the carbon source is carried out in a protective atmosphere, and the protective atmosphere includes at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas; (20) The step of removing the oxide of metal A includes pickling the product of the thermal reaction with an acid solution; (21) The step of removing the oxide of metal A includes pickling the product of the thermal reaction using an acid solution, the acid solution including at least one of hydrochloric acid, nitric acid, and sulfuric acid; (22) The molar ratio of the complex to the carbon source is 1:(0.01 to 10); (23) The thermal reaction is carried out at a temperature of 200°C to 950°C; (24) The thermal reaction is carried out with an incubation time of 1 hour to 24 hours; (25) The thermal reaction has a temperature rise rate of 1° C. / min to 20° C. / min.

9. 9. The method according to claim 7, further comprising the step of forming a coating layer on a surface of the silicon carbon composite material to obtain a negative electrode material.

10. The method according to claim 9, further comprising: (1) The step of forming a coating layer on the surface of the silicon carbon composite material includes sintering a mixture containing the silicon carbon composite material and polymer particles under a vacuum condition to form a coating layer; (2) The step of forming a coating layer on the surface of the silicon carbon composite material includes sintering a mixture containing the silicon carbon composite material and polymer particles under a vacuum condition to form a coating layer, the polymer particles including at least one of asphalt, resin, polyester-based polymer, and polyamide-based polymer; (3) The step of forming a coating layer on the surface of the silicon carbon composite material includes sintering a mixture containing the silicon carbon composite material and polymer particles under a vacuum condition to form a coating layer, and the mass ratio of the polymer particles to the silicon carbon composite material is 1:(0.1-10); (4) The step of forming a coating layer on the surface of the silicon carbon composite material includes sintering a mixture containing the silicon carbon composite material and polymer particles under a vacuum condition to form a coating layer, and the sintering temperature is 600°C to 1000°C; (5) The step of forming a coating layer on the surface of the silicon carbon composite material includes sintering a mixture containing the silicon carbon composite material and polymer particles under a vacuum condition to form a coating layer, and the sintering is performed with an incubation time of 1 hour to 24 hours; (6) The step of forming a coating layer on the surface of the silicon carbon composite material includes sintering a mixture containing the silicon carbon composite material and polymer particles under a vacuum condition to form a coating layer, and the sintering has a temperature increase rate of 1° C. / min to 20° C. / min; (7) The step of forming a coating layer on the surface of the silicon carbon composite material includes sintering a mixture containing the silicon carbon composite material and polymer particles under vacuum conditions to form a coating layer, and the vacuum conditions include a vacuum degree of less than 0.1 MPa.

11. The method according to claim 9, further comprising: (1) The step of forming a coating layer on the surface of the silicon carbon composite material includes synthesizing a polymer on the surface of the silicon carbon composite material by a chemical synthesis method to form a coating layer; (2) The step of forming a coating layer on the surface of the silicon carbon composite material includes synthesizing a polymer on the surface of the silicon carbon composite material using a chemical synthesis method to form a coating layer, and the polymer includes at least one of a resin-based polymer and a polyester-based polymer.

12. 10. The method according to claim 9, wherein the step of forming a coating layer on the surface of the silicon carbon composite material comprises forming a coating layer on the surface of the silicon carbon composite material by chemical vapor deposition of an organic carbon source.

13. A lithium ion battery comprising the negative electrode material according to claim 1 or 2.

Citation Information

Patent Citations

  • Negative electrode composite material of lithium ion battery and preparation method thereof

    CN107623116A

  • Silicon-carbon composite material and preparation method thereof

    CN109802120A

  • Porous silicon electrode and method

    JP2017520089A

  • Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

    JP2019169354A

  • Batteries with carbon-coated macroporous silicon anodes

    JP2020533729A